Efﬁciency of indolebutyric acid and different substrates in yerba mate cuttings - Teixeira, Marelise; Filter, Maíra; Périco, Eduardo; de Freitas, Elisete Maria; Sperotto, Raul Antonio (Iheringia, Série Botânica., 2018)
Ilex paraguariensis A.St.-Hil. is an arboreal species whose leaves are used in the preparation of mate and in the cosmetics and food industries. Due to diffi culty found in the sexual propagation of the species, this paper aimed to test effi ciency of indolebutyric acid (IBA) in saplings production from semi-woody cuttings. On the fi rst experiment, cuttings were taken from young plants, immersed in diff erent concentrations of IBA and established in substrate. On the second experiment, cuttings were established in four diff erent substrates previously submersed in IBA. A concentration of 3.0 mg L-1 of IBA and a substrate composed of biostabilized pine bark, limestone and vermiculite + carbonized rice hull, have shown a greater effi ciency in rooting of young I. paraguariensis saplings, and could be used to facilitate yerba mate propagation.